Kadar Urine Urea Nitrogen (UUN) sebagai prediktor mortalitas pada pasien luka bakar >20% di RSUP Prof. Dr. I. G. N. G. Ngoerah Denpasar - Grace Inriani Rongre; I Gusti Putu Hendra Sanjaya; Agustinus I Wayan Harimawan; Sianny Herawati (DiscoverSys Inc., 2022)
Background: Urine urea nitrogen (UUN) is an examination of nitrogen balance with the concept of calculating the amount of urea excreted through urine. The amount of urea that comes out of the urine is in line with the amount of protein breakdown in the body and the amount of protein that enters the body. This study aimed to evaluate UUN levels on days 1, 3 and 7 as a predictor of mortality in burn patients >20%. Methods: This study was an observational analytic retrospective study. Data were collected from January 2020 to December 2021. This study used secondary data from medical records of patients with IIAB-III degree burns with burn area > 20% TBSA treated at Prof. Dr. I. G. N. G. Ngoerah General Hospital for 2020-2021. Data were analyzed using SPSS version 21 for Windows. Results: The majority of burn patients were male, about 73.9%. The average age of burn patients is 48.26±15.95 years. On the first examination day, the UUN value was still low (29.4 mg/24 hours). Then on the 3rd day, there was an increase in the average UUN level, namely the maximum value of 61,987 mg/24 hours. Examination on the 7th day showed an increase in line with the previous day, namely the maximum value of 57,489 mg/24 hours. On day 1, the mean UUN value was higher in patients who died, while on days 3 and 7 the mean UUN level in patients with living outcomes was higher than in patients who died, but not significantly (p>0.05). Conclusion: Urine urea nitrogen levels on days 1, 3 and 7 in burn patients >20% at Prof. Dr. I. G. N. G. Ngoerah General Hospital showed an increasing trend. Urine urea nitrogen levels cannot be used to predict mortality in burn patients because the results were insignificant. Latar Belakang: Urin urea nitrogen (UUN) merupakan pemeriksaan keseimbangan nitrogen yang berkonsep pada perhitungan jumlah urea yang dieksresikan lewat urin. Jumlah urea yang keluar bersama urine sejalan dengan jumlah pemecahan protein dalam tubuh serta jumlah protein yang masuk dalam tubuh. Penelitian ini bertujuan untuk mengevaluasi kadar UUN hari ke-1,3, dan 7 sebagai prediktor mortalitas pasien luka bakar >20%. Metode: Studi ini merupakan studi retrospektif analitik observasional. Data dikumpulkan dari Januari 2020 hingga Desember 2021. Studi ini menggunakan data sekunder dari catatan rekam medis pasien luka bakar derajat IIAB-III dengan luas luka bakar > 20% TBSA yang dirawat di RSUP Prof. Dr. I. G. N. G. Ngoerah periode 2020-2021. Data dianalisis dengan SPSS versi 21 untuk Windows. Hasil: Mayoritas pasien luka bakar berjenis kelamin laki-laki yaitu sebesar 73,9%. Usia rata-rata pasien luka bakar yaitu 48,26±15,95 tahun. Pada pemeriksaan hari pertama didapatkan nilai UUN masih rendah (29,4 mg/24 jam). Kemudian pada hari ke-3 didapatkan peningkatan rata-rata kadar UUN yakni nilai maksimum 61.987 mg/24 jam. Pemeriksaan pada hari ke-7 menunjukkan peningkatan yang sejalan dengan hari sebelumnya yakni nilai maksimum 57.489 mg/24 jam. Pada hari ke-1, nilai rerata UUN lebih tinggi pada pasien meninggal, sedangkan pada hari ke 3 dan 7 kadar rerata UUN pasien dengan luaran hidup lebih tinggi dibandingkan pasien yang meninggal, namun tidak bermakna secara signifikan (p>0,05). Simpulan: Kadar UUN pada hari ke-1, 3 dan 7 pada pasien luka bakar >20% di RSUP Prof. Dr. I. G. N. G. Ngoerah menunjukkan adanya trend peningkatan. Kadar UUN tidak dapat dipakai sebagai prediktor mortalitas pada pasien luka bakar karena hasil tidak signifikan.